Procedure for the Design of Agrotourist Products to Contribute to Local Development - Lisbet Eunice Pérez Anzardo; Evelina Cardet Fernández; Irina Reyes Martínez; Damián Agüero Pintado (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2022)
Tourism products constitute an element of high incidence in the economies of all countries due to their multiplying nature and their potential as exportable resources. In addition, they represent a significant variable within the study of marketing, since they are the main component of the offer of any destination and around which revolve the rest of the policies that operational marketing follows. Regardless of the type of tourist product that is offered, it must be taken into account to satisfy the needs of tourists so that they can enjoy a unique experience that identifies and differentiates it from other products. The following article proposes, based on current trends, a procedure for the design of agro-tourism products that can be used in a general way, for the creation of tourism products. It comprises four structured phases in the form of a system and a fifth evaluation phase, which is present in the previous ones; which allows the correct planning, development, management and promotion of nature tourism products and their different segments, so that they can be inserted in a competitive market and are not only optional for the Sun and Beach modality, which is the one that is the most influx of tourists attracts globally. It also has in one of its stages the validation through the criteria of specialists of the design, importance and relevance of the tourist product, depending on its quality.